The history of spinocerebellar ataxia type 10 in Brazil: travels of a gene A história da ataxia espinocerebelar tipo 10 no Brasil: as viagens de um gene - Hélio A.G. Teive; Walter O. Arruda; Salmo Raskin; Tetsuo Ashizawa; Lineu César Werneck (Arquivos de Neuro-Psiquiatria)
The authors report the history of spinocerebellar ataxia 10 (SCA10), since its first report in a large Portuguese-ancestry Family with autosomal dominant pure cerebellar ataxia, till the final identification of further families without Mexican ancestry. These families present a quite different phenotype from those SCA10 families described in Mexico. Os autores apresentam a história da descoberta da ataxia espinocerebelar tipo 10 (AEC10) no Brasil, desde o primeiro relato em uma família com ancestrais portugueses com ataxia cerebelar pura, autossômica dominante, até a identificação de famílias sem ancestrais mexicanos. Essas famílias apresentam um fenótipo de AEC10, com ataxia cerebelar "pura", distinta daquele descrito nas famílias no México.